A serological survey of canine respiratory coronavirus in New Zealand. Issue 1 (2nd January 2020) - More, GD; Dunowska, M; Acke, E; Cave, NJ
ABSTRACT: Aims: To determine the seroprevalence of canine respiratory coronavirus (CRCoV) in New Zealand dogs, and to explore associations with age, sex, breed, month, and geographical region of sampling and reported presence of clinical signs suggestive of respiratory disease. Methods: A total of 1, 015 canine serum samples were randomly selected from submissions to a diagnostic laboratory between March and December 2014, and were analysed for CRCoV antibodies using a competitive ELISA. Logistic regression analysis was used to determine associations between seroprevalence of CRCoV and breed category, age, sex, sampling month, region, and reported health status of dogs. Results: Overall, 538/1, 015 (53.0%) samples were seropositive for CRCoV, with 492/921 (53.4%) positive dogs in the North Island and 46/94 (49%) in the South Island. Age of dog, sampling month, region, and presence of abnormal respiratory signs were included in the initial logistic regression model. Seroprevalence was higher in dogs aged ≥3 compared with ≤2 years (p < 0.01). The lowest seroprevalence was observed in July (30/105; 28.5%) and August (32/100; 32%), and the highest in June (74/100; 74%). Seroprevalence in dogs from Auckland was higher than in dogs from the Hawkes Bay, Manawatu, Marlborough, and Waikato regions (p < 0.05). Abnormal respiratory signs (coughing, nasal discharge, or sneezing) were reported for 28/1, 015 (2.8%) dogs sampled. Seroprevalence for CRCoV tended to be higher among dogs with respiratory signs (67.9 (95% CI = 47.6–83.4)%) than dogs with no reported respiratory signs (52.6 (95% CI = 49.5–55.7)%). Conclusions: Serological evidence of infection with CRCoV was present in more than half of the dogs tested from throughout New Zealand. Differences in CRCoV seroprevalence between regions and lack of seasonal pattern indicate that factors other than external temperatures may be important in the epidemiology of CRCoV in New Zealand. Clinical relevance: Our data suggest that CRCoV should be included in investigations of cases of infectious canine tracheobronchitis, particularly if these occur among dogs vaccinated with current vaccines, which do not include CRCoV antigens.